Economic and Performance Analysis of Bioethanol Production from Aren and Palm Biomass Using Ionic Liquid with SuperPro Designer as a Transportation Energy Transition Strategy - Maulidin, Ihsan; Utami, Amaliyah Rohsari I.; Sugiwati, Sri (TEKNIK, 2025)
This Increasing energy consumption has caused energy availability to become increasingly scarce, especially in Indonesia. Therefore, developing renewable energy sources, such as biofuels, is becoming increasingly important to support the energy transition in the transportation sector. One type of biofuel that is promising is bioethanol, which can be produced from biomass such as sugar palm and palm oil. However, the development of bioethanol still faces obstacles in terms of effectiveness, time, and production costs. Performance and economic analysis of bioethanol production from sugar palm and oil palm biomass with ionic liquid (IL) has been carried out using SuperPro Designer (SPD) software. This process begins with testing biomass characteristics to determine the most optimal sugar palm composition. Simulations with experimental conditions show that the optimal IL and biomass ratios are 1 g/g, resulting in ethanol concentrations of 92 g/L and 94 g/L, respectively, close to the theoretical results with 96% conversion of biomass to ethanol. Ethanol production on a factory scale shows cost reductions of up to 30% from initial prices. With the abundant availability of biomass, bioethanol production from sugar palm and palm oil has great potential to be developed in Indonesia, supporting the energy transition strategy in the transportation sector and reducing dependence on fossil fuels.